Lactiplantibacillus plantarum ameliorated the negative effects of a low-protein diet on growth performance, antioxidant capacity, immune status, and gut microbiota of laying chicks - Hou, Lele; Qiu, Huiling; Dong, Jihong; Liu, Huawei; Gao, Shansong; Chen, Fu (Frontiers in Microbiology, 2025)
This experiment was conducted to investigate the effects of adding Lactiplantibacillus plantarum to a low-protein diet on the growth performance, ability immune status, and intestinal microbiota of 0–21-day-old layer chickens. A total of 180 one-day-old healthy Hy-line brown laying chicks were randomly divided into three groups with three replicates each of 20 chicks. The control group was fed a basal diet containing 19% protein, the low-protein (LP) group was fed a diet containing 17% protein, and the probiotic (LPL) group was fed with the 17% protein diet supplemented with L. plantarum (1.0 × 109 CFU/kg). The growth performance, antioxidant capacity, immune status, and gut microbiota of laying chickens were detected. We found that L. plantarum supplementation increased the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), total antioxidant capacity (T-AOC), and levels of immunoglobulin (Ig) A, IgG, and interleukin-10 (IL-10) in serum of 17% protein +1.0 × 109 CFU/kg L. plantarum (LPL) compared to the 19% protein group (control). Furthermore, L. plantarum supplementation increased the liver index, GSH-Px and T-AOC activity in serum, and changed the microflora structure, diversity, and polyketose unit bioanabolic metabolism of 17% protein +1.0 × 109 CFU/kg L. plantarum (LPL) compared to the 17% protein group (LP). In conclusion, L. plantarum supplementation could compensate for the adverse effects of low-protein diets in chicks, and the combination of a low-protein diet and L. plantarum is a feasible way to reduce protein in the diet.